Economía digital en América Latina: Reflexiones sobre las concentraciones económicas en la región - Greco, Esteban (2022)
The article analyzes mergers and acquisitions in the digital economy in Latin America, in line with the international discussion and the new or reformulated theories of harm that have been emerging. It highlights the importance of the regional context and to not automatically transfer the criteria and conclusions of the international discussion to Latin American countries. Based on the analysis of cases of different agencies, it is remarked that preventive merger control in the region can be a tool that contributes to prevent new players in the digital economy, who bring innovation and new services, from encountering barriers.